NASA Robotic Mining Competition 2017 Systems Engineering Report; Badger Robotic Mining Team - Zeugner, David William (Proceedings of the Wisconsin Space Conference, 2018)
Held at Kennedy Space Center, NASA hosts their annual Robotic Mining Competition to challenge college students with designing and fabricating a robot suitable for mining in environments outside Earth. This year, the Badger Robotic Mining Team at UW-Madison competed for its second time in the competition. To prepare, team members continued work on their RMC 2016 miner, and after such prototyping developed a new robot for RMC 2017. The same mining strategy from the previous competition was used for RMC 2017. This paper summarizes the development of various elements of the mining robot.